Production of Monitoring Temperature and Humidity Device Based On Short Message Service (SMS) Using AWE.2020 - Kusuma Jaya, I Putu Wahyu Pranata; Widagda, I Gusti Agung (BULETIN FISIKA; Vol 22 No 1 (2021): BULETIN FISIKA February Edition, 2020)
It has been successfully created a device that can monitor the temperature and humidity of air through a mobile-based Short Message Service (SMS) with the name is AWE.2020. This tool consists of DHT22 temperature and humidity sensor, a GSM SIM800L module, and an Arduino Uno R3 microcontroller. The temperature and humidity readings will be processed by the Arduino Uno R3 microcontroller and the result will be sent as an SMS via GSM SIM800L module. To measure the accuracy of the prototype device (AWE.2020) a calibration was done with existing standard AWS device at Jembrana Climatology Station, Bali. Several parameters are used to measure the accuracy of this measuring instrument, such as regression analysis and statistical t-test. The performance of AWE.2020 depends of the signal quality of the provider. When the signal is good, the result of t-test and regression analysis of this tool show a high degree of accuracy; and vice versa. From the observations, as well as statistical t-tests it was found that the tool was accurate and precise to use but depends on provider signal which is used for.